2018
DOI: 10.1016/j.pld.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Pollination ecology in China from 1977 to 2017

Abstract: China is one of most biodiverse countries in the world, containing at least 10% of all angiosperm species. Therefore, we should anticipate a diverse, pollinator fauna. China also has a long history of applied ethnobiology, including a sustainable agriculture based on apiculture and plant-pollinator interactions. However, the science of pollination ecology is a far younger sub-discipline in China, compared to in the West. Chinese studies in pollination ecology began in the 1970s. For this review, we compiled a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…For example, some globallevel studies of plant-pollinator interactions and plant reproductive ecology included no or very few East Asian examples due to the lack of available data (Ollerton et al 2009;Ollerton 2012;Schleuning et al 2012;Rech et al 2016;Johnson et al 2017;Zanata et al 2017). Additionally, pollinators like hawkmoths and nectar-feeding birds have been poorly studied in East Asia (Johnson et al 2017;Ren et al 2018;Liu & Sun 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, some globallevel studies of plant-pollinator interactions and plant reproductive ecology included no or very few East Asian examples due to the lack of available data (Ollerton et al 2009;Ollerton 2012;Schleuning et al 2012;Rech et al 2016;Johnson et al 2017;Zanata et al 2017). Additionally, pollinators like hawkmoths and nectar-feeding birds have been poorly studied in East Asia (Johnson et al 2017;Ren et al 2018;Liu & Sun 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The study of plant-pollinator interactions and plant reproductive ecology in East Asia has been developing rapidly in recent decades (Barrett 2015;Ren et al 2018). Ren et al (2018) summarized the pollination research done so far in China, and suggested future directions it could take.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though China has a long history of ethnobotanical practices and a sustainable agricultural system based on apiculture and plant–pollinator interactions, pollination ecology is a young sub-discipline in China, only started in the 1970s. Ren et al. (2018) compile a complete pollination reference database in China including more than 600 published articles.…”
mentioning
confidence: 99%